COVID-19 PANDEMIC: CHALLENGES FACED HEALTHCARE PROVIDERS - Hatem Shabbab Almutairi, Abdulelah Gasim Hamali, Abdullah Mutlaq Alqthami, Marzouqha Aqeel Al Shammary, Nuran Mohammed Albarqi, Ghazal Ghassan Badroon, Reham Kalaf Alanizi, Athbah Mohammed Alwedehi,,; Nuran Mohammed Albarqi, Ghazal Ghassan Badroon, Mosfer Saleh Almoreah, Abdullah Mahdi Alzamanan, Abdullah Awad Mohamed Almasfuh, Mohammad Fehaid Al Mansour, Mohammed fahad Alotaibi, Khalid Hamoud Alharbi, (Chelonian Research Foundation, 2022)
Globally, the Covid-19 pandemic has posed hitherto unheard-of difficulties for management and healthcare professionals. This research looks at how the pandemic affected the front-line healthcare providers and how managers handled the situation. Key issues and management techniques were discovered through qualitative analysis of manager and healthcare professional interviews. The results show that healthcare workers experienced social stigma, psychological discomfort, increasing workloads, and a lack of necessary resources. Challenges pertaining to insufficient readiness, decision-making procedures, and resource distribution were faced by managers. But by putting methods like public awareness campaigns, educational programs, and managerial role reform into practice, managers showed resiliency and creativity. It became clear that cooperation, communication, and adaptability were essential for effective crisis management. In order to be ready for future pandemics, it is advised to make investments in human resource management, interdisciplinary teamwork, and healthcare infrastructure. Additionally, managers and employees should be encouraged to seek mental health support services. Key words: Covid-19 pandemic, healthcare professionals, managers, challenges, management strategies, resource allocation, resilience, collaboration, preparedness.